First report of wounded-tree beetle (Coleoptera: Polyphaga: Nosodendridae) in Baltic amber of the Sambian peninsula - Alekseev, Vitalii; Bukejs, Andris (Zootaxa, 2025)
The first Paleogene representative of the relictual family Nosodendridae is described and illustrated based on an inclusion in Eocene Baltic amber. The new species, Nosodendron (Dendrodipnis) andrushchenkoi sp. nov., is placed in the extant genus Nosodendron and compared with both extant and fossil congeners.